Kepailitan Akibat Cidera Janji Dalam PKPU : Studi Kasus PT Njonja Meneer Dalam Putusan Nomor 1397 K/Pdt.Sus-Pailit/2017 - Syah, Aurellia Zerikha (Media Hukum Indonesia (MHI), 2025)
Postponement of Debt Payment Obligations (PKPU) is a legal mechanism that allows debtors to restructure their debts through a peace agreement (composition) with creditors. However, when the debtor fails to perform the obligations stipulated in the agreement, such failure may be classified as a breach of contract (wanprestasi) and serve as a valid legal basis for creditors to file a bankruptcy petition. This study aims to analyze the legal provisions concerning the annulment of a composition agreement in PKPU and to examine the actions of PT Njonja Meneer that were deemed a breach of contract in the implementation of such agreement. The research adopts a normative juridical method with a statutory and case study approach, based on the Supreme Court Decision Number 1397 K/Pdt.Sus-Pailit/2017. The findings indicate that PT Njonja Meneer’s failure to substantially fulfill its payment obligations constituted a material breach of the court-approved agreement, thereby justifying the creditor’s petition for bankruptcy. The Supreme Court ruling reinforces that the execution of a peace agreement must be carried out in good faith, as failure to do so may result in the revocation of the agreement and a declaration of bankruptcy against the debtor.